Diadumenos statue from Vaison-la-Romaine, British Museum 01 - 14GTR (Wikimedia Commons, 2025)
Notice iconographique issue de Wikimedia Commons. Titre: Diadumenos statue from Vaison-la-Romaine, British Museum 01. Diadumenos statue in marble, being a Roman version of a Greek bronze original from 440-430 BC. Found by the Roman theatre at Vaison-la-Romaine, France, possibly originally from a nearby villa. British Museum item GR 1870, 0712.1
Droits : Licence Creative Commons Zero, Public Domain Dedication via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures